The impact of public private partnership on urban development in Zimbabwe’s local authorities: a case study of stands allocation at Victoria Falls municipality - Dube, Nontokozo (Midlands State University, 2018)
The endeavour of this study is to probe the impact of Public Private Partnership (PPP) on urban development in Zimbabwe’s Local Authorities using the recent partnership between the Victoria Falls Municipality (VFM) and the Commercial Bank of Zimbabwe (CBZ) on housing development. This study therefore seeks to unravel the effects of Public Private Partnership, whether the land allocation process was line with the Local Government policy, was fairness observed and were the general population availed the opportunity to participate in this ongoing development. Notably the Public Private Partnership play a very crucial role in Zimbabwe in terms of financing large infrastructural development. The government of Zimbabwe cannot rely only on the tax base to fund the large infrastructural development projects that is where the Public Private Partnership comes into play so to ensure equitable service delivery. The study also noted that in Zimbabwe there is lack of legal framework which should be a guideline to these Public Private Partnerships. On this scenario this study suggests that the government of Zimbabwe should craft laws which will serve as a guideline for the effectiveness of Public Private Partnership so that power cannot be abused at any level and ensuring the full protection of its citizenry.